Late Diagnosis of Hirschsprung's Disease: Definition and Implication on Core Outcomes - Tan, Yew-Wei; Chacon, Carmen Sofia; Geoghegan, Niamh; Saxena, Amulya; Clarke, Simon; Haddad, Munther; Choudhry, Muhammad (European Journal of Pediatric Surgery, 2022)
Introduction Late diagnosis of Hirschsprung's disease (LDHD) may carry a poor prognosis. Its definition remains unclear and its implication on HD-related core outcomes has not been fully reported.Methods A single-center 20-year series was reviewed to include HD with follow-up of 1 year or more post pull-through (PT) and aged 5 years or older. We investigated six core outcomes derived from NETS1HD study by comparing the groups dichotomized by four time points using age at diagnosis (44-week gestation, 6 months, 1 year, and 3 years). Following establishment of definition of LDHD, the outcomes and complications were compared with timely diagnosis of HD (TDHD).Results Forty-nine out of eighty-six HD were included. The definition of LDHD was found to be HD diagnosed at 1 year of age or later because 3/6 core outcomes were significantly worse than TDHD. Nine patients (18%) had LDHD—median age at diagnosis 42 months (12–89) and PT performed at 57 months (12–103), mostly Soave (73%); a covering stoma was performed in 7/9, significantly higher than TDHD in 10/40 (p = 0.001). LDHD was associated with increased unplanned surgery (78% vs. 30%, p = 0.019), fecal incontinence (100% vs. 62%, p = 0.01), and permanent stoma (33% vs. 5%, p = 0.037). Major complications (56% vs. 20%, p = 0.043) and redo PT (33% vs. 5%, p = 0.037) were also higher in LDHD.Conclusion LDHD could be defined as HD diagnosis at or over 1 year of age. LDHD was associated with more preoperative stoma, major postoperative complications, unplanned reoperation, and worse HD-related core outcomes.
Keywords: Hirschsprung's disease; late diagnosis; core outcome; age; complication